Synthesis of Schiff Bases under Ultrasound-Irradiation - YUYE, YU (Asian Journal of Chemistry, 2010)
Ultrasound irradiation promoted the formation of a series of Schiff bases in the condensation reaction between substitute benzaldehydes and substitute anilines. Substitute benzaldehydes and substitute anilines, containing either electron-withdrawing or electron-releasing groups, were assessed to identify any substituent effect on the formation of the Schiff bases. This new procedure is environmentally benign because no solvent was employed in the transformations.